Impact of direct laryngoscopy vs. videolaryngoscopy on signal quality of recurrent laryngeal nerve monitoring in thyroid surgery: a randomised parallel group trial. (27th September 2022) - Kriege, M.; Hilt, J. A.; Dette, F.; Wittenmeier, E.; Meuser, R.; Staubitz, J. I.; Musholt, T. J.
Summary: In thyroid surgery, intra‐operative neuromonitoring signals of the recurrent laryngeal nerve can be detected by surface electrodes on a tracheal tube positioned at the vocal fold level. The incidence of difficult tracheal intubation in patients undergoing thyroidectomy for nodular goitre ranges from 5.3% to 20.5%. The aim of this study was to compare videolaryngoscopy with conventional direct laryngoscopy as methods for proper placement of the surface electrode to prevent insufficient intra‐operative nerve signal quality. In this prospective randomised trial, adult patients requiring tracheal intubation during thyroid surgery were randomly allocated to two groups of C‐MAC ® (Macintosh style blade) videolaryngoscope or direct laryngoscopy using the Macintosh laryngoscope. Primary outcome was the incidence of insufficient signal electromyogram amplitude level (< 500 μV) after successful tracheal intubation. A total of 260 (130 per group) participants were analysed. An insufficient signal was more frequent with direct laryngoscopy (35/130, 27%), compared with C‐MAC (12/130, 9%, p < 0.001). First‐pass tracheal intubation success rate was lower with direct laryngoscopy (86/130 (66%)) compared with the C‐MAC (125/130 (96%)) (p < 0.0001). Cormack and Lehane grade ≥ 3 was observed more frequently with direct laryngoscopy (16/130 (12%)), compared with the C‐MAC (0/130, (0%)) (p < 0.0001). The results suggest that videolaryngoscopy has an impact on the quality of the initial intra‐operative neuromonitoring signal in patients undergoing thyroid surgery, and this technique can provide optimised surface electrode positioning.